2012
DOI: 10.1128/mcb.06785-11
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A) Binding Protein C1 Is Essential for Efficient L1 Retrotransposition and Affects L1 RNP Formation

Abstract: Poly(A) binding proteins (PABPs) specifically bind the polyadenosine tail of mRNA and have been shown to be important for RNA polyadenylation, translation initiation, and mRNA stability. Using a modified L1 retrotransposition vector, we examined the effects of two PABPs (encoded by PABPN1 and PABPC1) on the retrotransposition activity of the L1 non-long-terminal-repeat (non-LTR) retrotransposon in both HeLa and HEK293T cells. We demonstrated that knockdown of these two genes by RNA interference (RNAi) effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 82 publications
2
74
0
Order By: Relevance
“…The knockdown of hnRNPL led to an increase in the levels of mouse LINE-1 RNA and ORF1p and an increase in the retrotransposition of engineered LINE-1 in cultured cells (346). In addition, the poly-A binding protein C1 (PABPC1) interacts with the LINE-1 RNA and is required for LINE-1 RNP formation and efficient retrotransposition (347). Finally, cell culture assays have shown that human LINE-1 and mouse IAP mobility are restricted by the RNase activity of human RNase L, a member of the 2’,5’-oligoadenylate (2–5A) synthetase (OAS)-RNase L system, initially described for restricting viral infections during the interferon antiviral response (348).…”
Section: The Identification Of Host Factors That Regulate Line-1 Retrmentioning
confidence: 99%
“…The knockdown of hnRNPL led to an increase in the levels of mouse LINE-1 RNA and ORF1p and an increase in the retrotransposition of engineered LINE-1 in cultured cells (346). In addition, the poly-A binding protein C1 (PABPC1) interacts with the LINE-1 RNA and is required for LINE-1 RNP formation and efficient retrotransposition (347). Finally, cell culture assays have shown that human LINE-1 and mouse IAP mobility are restricted by the RNase activity of human RNase L, a member of the 2’,5’-oligoadenylate (2–5A) synthetase (OAS)-RNase L system, initially described for restricting viral infections during the interferon antiviral response (348).…”
Section: The Identification Of Host Factors That Regulate Line-1 Retrmentioning
confidence: 99%
“…Moreover, knockdown experiments of the corresponding mRNA result in significant reduction of L1 retrotransposition rate. By opposition, in PAIP2 knockdown cells, an inhibitor of PABPC1, a 2-fold L1 retrotransposition increase has been observed (136). Taken together, these results suggest that PABPC1 is essential for the formation of the RNP, and any depletion of PABPC1 can lead to defect in the RNP formation and in the achievement of a retrotransposition cycle (136).…”
Section: Other Line-1 Regulators Described In Somatic Cellsmentioning
confidence: 75%
“…By opposition, in PAIP2 knockdown cells, an inhibitor of PABPC1, a 2-fold L1 retrotransposition increase has been observed (136). Taken together, these results suggest that PABPC1 is essential for the formation of the RNP, and any depletion of PABPC1 can lead to defect in the RNP formation and in the achievement of a retrotransposition cycle (136). As it is known that PABPC1 can shuttle between the cytoplasm and the nucleus, the authors assumed that PABPC1 might provide a direct trafficking function for the RNP nuclear translocation, an essential step to complete a retrotransposition cycle (136).…”
Section: Other Line-1 Regulators Described In Somatic Cellsmentioning
confidence: 92%
See 1 more Smart Citation
“…By applying the same technique to other ORF1p/ORF2p mutants, we should be able to further dissect the L1-host interactome and catalog the relationships with respect to specific step(s) of the L1 lifecycle. A complementary approach includes coupling large scale RNAi with L1 induction in suspension cell culture, since we have been able to easily generate shRNA-L1 co-expression vectors 38 . This will allow us to test which L1 RNP constituents affect the remaining complement of proteins’ abilities to co-purify with the L1 RNP, as well as to assay effects on retrotransposition activity in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%